Effects of small-sided games on some recovery markers in football - Tayyar Karadağ; Süleyman Patlar; Ahmet Bayrak (Physical Education of Students)
Background and Study Aim. Small-sided games (SSGs) are widely used in football training to replicate match conditions while controlling the physical load on players. Variations in the number of players during these games can significantly influence key recovery markers. This study aims to investigate the effects of variations in player numbers on maximal heart rate, blood lactate levels, and perceived exertion in small-sided games acutely applied in football.